Malondialdehyde Expression in HT29 Cells with Blastocystis sp. Exposure - Rusjdi, Selfi Renita; Irawati, Nuzulia; Yanwirasti, Yanwirasti; Hilbertina, Noza (Faculty of Medicine, Universitas Jember, 2024)
Blastocystis sp. is one of the intestinal protozoa that is frequently found in stool specimens of colorectal cancer patients. This protozoan infection will trigger the host cell defense response to produce Reactive Oxygen Species (ROS) which causes oxidative stress. Oxidative stress can cause and aggravate colorectal cancer. Lipid peroxidation is one of the best indicators of ROS levels. Malondialdhyde is its end product so it is used as a marker of oxidative stress. This study aims to determine the exposure of Blastocystis sp. on malondialdehyde expression in colorectal cancer cell line HT29. This research is an experimental study in vitro. HT29 cells were treated with various concentrations of Blastocystis sp. antigen (0.005 Î¼g/ml, 0.01 Î¼g/ml, 0.05 Î¼g/ml, 0.1 Î¼g/ml and 0.5 Î¼g/ml) for 72 hours. Malondialdehyde expression was examined using spectrophotometric method. Data analysis was performed using One Way Anova test. The results of the study are the mean expression of malondialdehyde in nmol/ml. The mean malondialdehyde levels of the control group, treatment with concentrations of 0.005 Î¼g/ml, 0.01 Î¼g/ml, 0.05 Î¼g/ml, 0.1 Î¼g/ml and 0.5 Î¼g/ml were 3.134 nmol/ml, 2.682 nmol/ml, 2.556 nmol/ml, 2.744 nmol/ml, 2.84 nmol/ml and 3.286 nmol/ml respectively. The conclusion is that there is an effect of exposure to Blastocystis sp. on malondialdehyde expression of HT29 cells. Keywords: Blastocystis sp., HT29, malondialdehyde